Analyzing the Delivery, Support, and Service (DSS) Domain of UNSRAT Information System using COBIT 5: Identifying Gaps and Opportunities for Improvement - Mahardika Inra Takaendengan; Dodisutarma Lapihu; Ramadhan Paninggalih; Adrian Philip Marthinus (PT. Tech Cart Press, 2023)
This research paper presents an analysis of the UNSRAT (Universitas Sam Ratulangi) information system using the COBIT 5 (Control Objectives for Information and Related Technologies) framework, specifically focusing on the Delivery, Support, and Service (DSS) domain. The study aims to identify the strengths, gaps, and areas for improvement within the information system based on the perceptions of 20 respondents. The research methodology involves data collection through a questionnaire, followed by data analysis using COBIT 5 principles. The findings reveal several strengths, including well-defined strategic goals, a comprehensive service catalog, and effective change management processes. However, gaps such as stakeholder alignment, proactive incident management, and regular system performance evaluation were identified. Based on these findings, five recommendations were proposed to enhance the information system, including stakeholder engagement, incident management process improvement, service catalog enrichment, establishment of Service Level Agreements (SLAs), and the implementation of a continuous improvement framework. Implementing these recommendations will contribute to an optimized and user-centric information system, aligning with UNSRAT's mission and supporting its overall objectives.